Solid reverse phase catalyst and its preparation method and application in catalyzing low-temperature carbon dioxide methanation
By uniformly dispersing the solid reverse phase catalyst of oxide nanoparticles on the metal support, the problems of low-temperature activity and high-temperature inactivation of traditional catalysts are solved, and efficient CO2 methanation below 200°C is achieved, and the stability is maintained for a long time is maintained. and highly selective.
Patent Information
- Application Number
- CN202310129152.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-17
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-02-17
AI Technical Summary
The existing CO2 methanation catalysts have low activity under low temperature conditions, and high temperature operation will promote side reactions and increase the cost of methane separation. Traditional catalysts can achieve higher activity at high temperatures, but are prone to inactivation.
Design a solid reverse phase catalyst, which is supported by oxide nanoparticles on a metal support, and is prepared by hydrothermal method, co-precipitation method and in-situ precipitation method to form a nano-oxide/metal reverse phase interface structure, and the molar of the phase metal is loaded. The fraction is between 0.01 and 30%, and high conversion and high selectivity are achieved below 200°C.
High conversion and high selectivity at low temperatures of 200°C and below, methane selectivity exceeds 99%, maintaining stability during 1500 hours of operation, reducing the requirements of reaction temperature and pressure.
Smart Images

Figure BDA0004083162240000091 
Figure BDA0004083162240000101 
Figure HDA0004083162250000011
Abstract
Description
Technical Field
[0001] The invention relates to a solid reverse phase catalyst and a preparation method thereof, as well as application of the solid reverse phase catalyst in a multiphase catalytic carbon dioxide hydrogenation and methanation reaction. Background Art
[0002] Human beings' excessive exploitation and use of fossil energy have caused a large amount of CO2 emissions, which has triggered a series of serious environmental problems such as abnormal climate, rising sea levels, glacier retreat, permafrost melting, and reduced plant and animal diversity. Capturing CO2 from factory exhaust and converting it into methane, methanol or other high-value chemicals is a win-win solution to environmental pollution and energy shortages. Among them, CO2 methanation has broad prospects in energy conversion and H2 energy storage applications.
[0003] ΔH 298 K = -165.1 kJ mol -1 (1)
[0004] ΔH 298 K =41.2 kJ mol -1 (2)
[0005] The thermodynamic enthalpy change of the CO2 methanation reaction (Equation 1) is -165.1 kJ mol -1 , which is a strongly exothermic reaction, so the reaction process is thermodynamically favorable at low temperatures. However, the reduction of CO2 to CH4 involves the transfer of eight electrons, and there is a high kinetic barrier in the hydrogenation process. It is usually necessary to work at a higher operating temperature (>300°C) to obtain a satisfactory CH4 space-time yield. However, too high a reaction temperature will not only inhibit CO2 methanation, but also facilitate the occurrence of the side reaction reverse water vapor change reaction (Equation 2). The generated byproduct CO will require additional separation and purification steps for CH4 in subsequent energy utilization, increasing the cost of CH4 as a fuel and weakening the application advantage of CO2 methanation. Therefore, the design and development of inexpensive, low-temperature, and efficient CO2 methanation catalysts can effectively promote the practical application of CO2 methanation and improve competitiveness.
[0006] The design of traditional low-temperature CO2 hydrogenation to methane catalysts mainly revolves around metal / oxide supported catalysts formed by metal nanoparticles and oxide substrates. On the interface of traditional metal / oxide catalysts, some oxygen-containing intermediates adsorbed on oxide sites usually have extremely high thermodynamic stability, high hydrogenation conversion energy barriers, and are easy to occupy active centers, which greatly reduces the low-temperature activity of the catalyst. The reverse oxide / metal catalyst formed by metal carrier-supported oxide clusters has an interfacial spatial structure different from that of traditional metal / oxides, and has the potential to increase the conversion rate of oxygen-containing intermediates, and even change the reaction path and improve catalyst performance. In addition, in practical applications, the cost of some metals (such as iron, cobalt, nickel, copper, etc.) is basically the same as or even lower than that of oxides. Therefore, the design of reverse oxide / metal structures can provide new opportunities for the creation of efficient CO2 hydrogenation catalysts.
[0007] The present invention provides a solid reverse phase catalyst in which oxide nanoparticles are loaded on a metal carrier and a preparation method thereof. The reverse phase catalyst can react with the metal carrier under low temperature conditions of 200°C or below and high reaction space velocity (127,000 h -1 ) has a CO2 methanogenic activity that exceeds that of most reported catalysts, with a methane selectivity of >99% and a methane production rate of up to 50 g CH4 / g cat / h, and the reverse phase catalyst was confirmed to have excellent stability during long-term operation of 1500h. Summary of the invention
[0008] The purpose of the present invention is to provide a solid reverse phase catalyst and a preparation method thereof. The catalyst of the present invention can realize a CO2 methanation process with high conversion rate, high selectivity and high stability under low temperature conditions.
[0009] The technical solution of the present invention is as follows:
[0010] A solid reverse phase catalyst, using a metal that dissociates hydrogen as a carrier, and a nano-oxide that generates oxygen vacancies to adsorb and activate carbon dioxide as a support phase, wherein the nano-oxide is uniformly dispersed on the surface of the metal carrier, and has a nano-oxide / metal reverse phase interface structure;
[0011] in,
[0012] The carrier metal is selected from one or more of cobalt, nickel, aluminum, copper and ruthenium;
[0013] The supported phase nano-oxide is selected from one or more of titanium oxide, aluminum oxide, manganese oxide, cerium oxide, zirconium oxide, silicon oxide, and tungsten oxide;
[0014] Based on the total molar amount of the metal in the carrier and the supported phase, the molar fraction of the metal in the supported phase is 0.01 to 30%.
[0015] The preparation method of the solid reverse catalyst described in the present invention comprises: preparing a carrier precursor by a hydrothermal method or a coprecipitation method under the conditions of a suitable precipitant and a solvent; preparing a nano-oxide dispersion by a sol method under the conditions of a suitable precipitant, a solvent and a protective agent; in-situ depositing or impregnating the nano-oxide on the carrier precursor by in-situ precipitation, excess volume impregnation and the like, and the obtained powdered solid is then subjected to the steps of roasting and reduction, and the nano-oxide with a relatively small proportion is uniformly dispersed on the surface of the metal carrier, thereby obtaining a solid reverse catalyst.
[0016] Preferably, the method for preparing the solid reverse phase catalyst of the present invention comprises the following steps:
[0017] (1) Synthesis of Nano-Oxides
[0018] The precursor salt of the load phase is dissolved in a solvent, and the obtained solution (concentration 0.01-5 mol / L) is added to a precipitant solution (concentration 0.01-5 mol / L) to obtain a hydroxide sol; the obtained hydroxide sol is added to ethanol to obtain a hydroxide-ethanol sol; the hydroxide-ethanol sol is then dispersed in a mixed solution of oleic acid / oleylamine / ethanol, stirred evenly, transferred to an autoclave, sealed, and subjected to solvent thermal treatment at 80-220° C. for 1-24 h, after which a solid product is collected, washed with deionized water until the pH of the washing solution is neutral, and freeze-dried to obtain a nano-oxide, which is dispersed in ethanol to obtain a nano-oxide dispersion for standby use;
[0019] In step (1), the precursor salt of the supported phase is selected from one or more of titanium tetrachloride, tetrabutyl titanate; aluminum nitrate, hydrated aluminum nitrate, aluminum chloride; manganese nitrate, hydrated manganese nitrate, manganese chloride; cerium nitrate, hydrated cerium nitrate, cerium chloride; zirconium nitrate, hydrated zirconium nitrate, zirconium chloride; tetraethyl orthosilicate; ammonium metatungstate, sodium tungstate, tungsten chloride;
[0020] The solvent is selected from one or more of water, methanol, ethanol, butanol, tetrahydrofuran, and methyl tert-butyl ether;
[0021] The precipitant is selected from one or more of ammonium carbonate, ammonia water, urea, sodium hydroxide, sodium bicarbonate, ammonium oxalate and oxalic acid;
[0022] (2) Synthesis of solid reverse phase catalyst (in situ precipitation method)
[0023] The precursor salt of the carrier is dissolved in a solvent, and the nano-oxide dispersion prepared in step (1) is added dropwise to the obtained solution (concentration 0.01-5 mol / L), and then a precipitant solution (concentration 0.01-5 mol / L) is added dropwise under stirring, and the pH is controlled to be 9, followed by aging at room temperature, filtering, washing, drying, calcining in static air, and reducing in a hydrogen atmosphere after calcination to obtain a solid reverse phase catalyst;
[0024] In step (2), the precursor salt of the carrier is selected from one or more of cobalt nitrate, hydrated cobalt nitrate, cobalt chloride, nickel nitrate, hydrated nickel nitrate, nickel chloride, copper nitrate, hydrated copper nitrate, copper chloride, and ruthenium chloride;
[0025] The solvent is selected from one or more of water, methanol, ethanol, butanol, tetrahydrofuran, and methyl tert-butyl ether;
[0026] The precipitant is selected from one or more of ammonium carbonate, ammonia water, urea, sodium hydroxide, sodium bicarbonate, ammonium oxalate and oxalic acid;
[0027] The preferred aging time is 1 to 24 hours;
[0028] The preferred drying temperature is 40 to 200°C and the drying time is 1 to 24 hours;
[0029] The preferred calcination temperature is 200-600°C and the time is 1-12h;
[0030] The preferred reduction temperature is 200-700°C, and the time is 1-6 hours; the preferred hydrogen concentration in the reducing atmosphere is in the range of 5-100%, and the total flow rate is in the range of 5-100 ml / min;
[0031] The particle size of the prepared solid reverse phase catalyst is 10 to 200 meshes.
[0032] The solid reverse phase catalyst of the present invention can be applied to the carbon dioxide methanation reaction. The specific application method is:
[0033] The solid reverse phase catalyst is placed in a fixed bed reactor, and a reaction gas with a molar ratio of carbon dioxide to hydrogen of 1:4 is introduced at a volume space velocity of 9000-127000 h -1 , reaction pressure range is normal pressure ~ 6Mpa, reaction temperature range is 25 ~ 450℃;
[0034] The catalyst stability test results show that the operation is stable for 1500h, the carbon dioxide conversion rate is maintained at about 90%, the methane selectivity is >99%, the preferred reaction temperature is 200°C, and the pressure is normal pressure.
[0035] The advantages of the present invention are:
[0036] The prepared oxide / metal reverse phase catalyst can catalyze the methanation reaction of carbon dioxide with high conversion rate, high selectivity and high stability under low temperature and normal pressure conditions not exceeding 200°C, and the conversion rate of carbon dioxide is greater than 80% and the methane selectivity is greater than 99% under high space velocity conditions. The conventional metal / oxide catalysts of the same period need to reach the activity of the present invention under 250°C or higher temperature and pressure conditions to complete. In addition, the solid reverse phase catalyst prepared by the present invention has good stability in the reaction system of carbon dioxide hydrogenation and can be used for a long time or repeatedly used in cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Thermodynamic diagrams of CO2 methanation reaction and side reaction reverse water vapor change reaction as a function of temperature are given.
[0038] Figure 2 In one embodiment, the catalyst reacts at different temperatures.
[0039] Figure 3 It is the reaction result of the catalyst at different volume space velocities in one embodiment.
[0040] Figure 4 The test results of CO2 conversion and CH4 selectivity over a catalyst period of 1500 hours in one embodiment are shown.
[0041] Figure 5 The following are the results of a study on the effects of different precipitants on the methanation activity of a reverse phase catalyst in one embodiment.
[0042] Figure 6 The figure is a comparison result of the methanation activities of metal oxide cluster catalysts supported on different metal supports in one embodiment.
[0043] Figure 7 The figure is a comparison result of the methanation activity of a binary reverse phase catalyst and a conventional forward catalyst in one embodiment.
[0044] Figure 8 This is the HAADF-STEM image of the catalyst prepared in Example 1. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other technical schemes obtained by ordinary technicians in the field belong to the scope of protection of the present application.
[0046] Traditional methanation catalysts are usually prepared by impregnation method, liquid phase reduction method and other methods. After the catalysts prepared by this method are calcined and reduced, the metal components with a small proportion are dispersed on the oxide carrier in the form of nanoparticles to form a metal / oxide interface structure. Traditional carbon dioxide methanation catalysts usually use oxides such as cerium oxide, zirconium oxide, aluminum oxide, silicon oxide, and titanium oxide as the bulk phase to provide oxygen vacancies to dissociate carbon dioxide, accounting for about 50% to 99.9% of the catalyst molar fraction. Metal iron, cobalt, nickel, copper, ruthenium, rhodium, palladium, platinum, etc. are used as catalyst support phases to dissociate hydrogen, accounting for about 0.01% to 30% of the catalyst molar fraction. Traditional forward catalysts often require temperatures above 250°C to catalyze the methanation reaction, and the active centers of the loaded nanoparticles are easily agglomerated and deactivated in a highly exothermic reaction system. In addition, the highly unsaturated coordination of the nanoparticles also makes the catalyst prone to carbon deposition and deactivation.
[0047] The present invention uses one or more metals that dissociate hydrogen as the bulk phase and an oxide that generates oxygen vacancies to adsorb and activate carbon dioxide as the supporting phase. The obtained reverse phase catalyst can achieve the carbon dioxide methanation process with high activity and selectivity at a high space velocity below 200°C, and has high temperature cycle stability of 450 degrees. The metal center exists in the form of a bulk phase, and the surface coordination unsaturation is reduced, which inhibits the formation of carbon deposits. In a specific embodiment, the volume space velocity is 9000 to 127000h -1 , the conversion rate of carbon dioxide is >80%, the selectivity of methane is >99%, and the stability exceeds 1500h. The specific synthesis method is as follows:
[0048] 1. Synthesis of Nano-Oxides
[0049] One or more corresponding precursor salts or hydrates of metals that generate oxygen vacancies to adsorb activated carbon dioxide are dissolved in a solvent at a certain concentration (between 0.01 mol / L and 5 mol / L), stirred until completely dissolved, and then added to a precipitant solution to obtain a hydroxide sol, and the obtained sol is added to ethanol to obtain a hydroxide-ethanol sol. A certain amount of hydroxide sol is dispersed in a mixed solution of oleic acid: oleylamine: ethanol and stirred evenly, and transferred to a 100 ml polytetrafluoroethylene-lined autoclave. Subsequently, the autoclave is sealed and solvent-thermally treated at a certain temperature (80°C-220°C) for a period of time (1-24h), and the obtained precursor is washed with deionized water several times until the pH of the washing solution is neutral, freeze-dried overnight, and nano-oxides are obtained, which are then dissolved in ethanol to obtain a transparent dispersion of nano-oxides.
[0050] The above method is suitable for the synthesis of the following nano oxides or mixed oxides (titanium oxide, aluminum oxide, manganese oxide, cerium oxide, zirconium oxide, silicon oxide, tungsten oxide, etc.).
[0051] 2. Preparation of carrier oxide
[0052] 2.1 Hydrothermal method
[0053] Dissolve one or more corresponding precursor salts or hydrates of metals that dissociate hydrogen (cobalt, nickel, aluminum, copper, ruthenium) in a solvent at a certain concentration (between 0.01 mol / L and 5 mol / L), stir until completely dissolved, and transfer to a 100 ml polytetrafluoroethylene-lined autoclave. Dissolve a certain amount of precipitant in 50 ml of solvent and add it to the above suspension to form a stock solution. Seal the autoclave and hydrothermally treat it at a certain temperature (80°C-220°C) for a period of time (1-24h). Wash the resulting precursor with deionized water several times until the pH of the washing solution is neutral, and freeze-dry overnight to obtain a metal carrier oxide.
[0054] 2.2 Coprecipitation method
[0055] One or more corresponding precursor salts or hydrates of metals that dissociate hydrogen (cobalt, nickel, aluminum, copper, ruthenium) are dissolved in a solvent at a certain concentration (between 0.01 mol / L and 5 mol / L), and ultrasonically stirred until completely dissolved. Under vigorous stirring, an appropriate amount of precipitant solution is added dropwise to the precursor salt solution. After the addition is completed, stirring is continued for 4 hours, and then centrifugally washed three times with anhydrous ethanol, dried in an oven, ground, and calcined in a muffle furnace to obtain a metal support oxide.
[0056] 3. Synthesis of reverse phase catalyst
[0057] 3.1 In situ deposition of metal precursors in nanoparticle solution
[0058] One or more corresponding precursor salts or hydrates of metals (cobalt, nickel, aluminum, copper, ruthenium) that dissociate hydrogen are dissolved in a solvent at a certain concentration (between 0.01mol / L and 5mol / L), and ultrasonic stirring is performed until completely dissolved. Then a certain amount of the nano oxide suspension prepared in step 1 is added dropwise to the above solution at a certain molar ratio. Under vigorous stirring, a precipitant solution of a certain concentration is added dropwise to the suspension, and the pH value is controlled to be about 9. The obtained precipitate is further aged for 1 hour at room temperature and then filtered, and then washed with deionized water at room temperature. The obtained material is dried in air overnight and then calcined in static air. After the calcination is completed, it is reduced in a hydrogen atmosphere, and the reduced nano oxide is loaded on a metal solid to obtain the prepared reverse phase catalyst.
[0059] 3.2 Over volume impregnation
[0060] The metal support oxide powder prepared in step 2 (or the metal support after reduction passivation in step 2) is dispersed in 100 mL of anhydrous ethanol. Then a certain amount of the nano oxide suspension prepared in step 1 is added dropwise to the above solution in a certain molar ratio. Then stir for 0.5 h, and then ultrasonically treat for 1 h to achieve good dispersion of the slurry. Then, the slurry is condensed and refluxed at 70 ° C for 2 h. After that, the solution is spin-dried, and the obtained precipitate is freeze-dried overnight. After freeze-drying, it is reduced in a hydrogen (residual nitrogen) atmosphere, and the reduced nano oxide is loaded on a metal solid to obtain the prepared catalyst.
[0061] 3.3 Monolithic Catalyst
[0062] A sheet of nickel foam, copper foam or cobalt foam with a length of 3 cm, a width of 2 cm and a thickness of 2 mm was ultrasonically treated with diluted hydrochloric acid (2 mol / L), ethanol and deionized water for 30 min. The treated sheet carrier was immersed in the hydroxide ethanol sol in step 1, and after stirring, it was transferred to a 100 mL polytetrafluoroethylene lined autoclave. Subsequently, the autoclave was sealed and heat-treated for a period of time (1-12 hours) at a certain temperature (80-200° C.), and the obtained sheet metal foam was washed several times with deionized water, and the obtained material was dried overnight in air and then calcined in static air. After the calcination was completed, it was reduced in a hydrogen atmosphere, and the sheet material of the reduced nano oxide supported on the metal foam carrier was the prepared reverse catalyst.
[0063] In the present invention, the loading amount refers to the percentage of the amount of the loaded phase metal on the carrier to the total amount of the catalyst. The loading amount is calculated as follows: loading amount = amount of the loaded phase metal / total amount of the catalyst × 100%.
[0064] In the present invention, the particle size of the solid catalytic carrier is 10-200 mesh (20 mesh, 30 mesh, 60 mesh, 80 mesh, 100 mesh, 150 mesh); it is placed in the gas-solid phase to carry out the carbon dioxide methanation reaction.
[0065] After room temperature, the reaction gas with a molar ratio of carbon dioxide to hydrogen of 1:4 is introduced, and the volume space velocity is 9000 to 127000h -1 , the reaction pressure ranges from normal pressure to 6Mpa, and the reaction temperature ranges from 25°C to 450°C.
[0066] In a specific embodiment, the catalyst stability test results show that the operation is stable for 1500 hours, the carbon dioxide conversion rate is maintained at about 90%, the methane selectivity is>99%, the reaction temperature is 200°C, and the pressure is normal pressure.
[0067] Hereinafter, embodiments of the present application will be described in more detail with reference to examples and comparative examples.
[0068] Example 1
[0069] Dissolve zirconium chloride and manganese chloride in 50mL water at a concentration of 0.075mol / L, stir until completely dissolved, add zirconium chloride and manganese chloride solutions to 50mL 2.5% ammonia solution and stir for 2h to obtain zirconium hydroxide and manganese hydroxide sols, and finally add to 20mL anhydrous ethanol to obtain ethanol zirconium and ethanol manganese sols. Add 5g of ethanol zirconium and ethanol manganese sols to a mixed solution of oleic acid: oleylamine: ethanol (40mL: 5mL: 5mL) and stir evenly, then transfer to a 100ml polytetrafluoroethylene-lined autoclave. Subsequently, seal the autoclave and heat at 200℃ for 12h, wash the resulting precipitate with deionized water several times until the pH of the washing solution is neutral, freeze-dry overnight to obtain nano zirconium oxide manganese, and then disperse it in ethanol to obtain a nano zirconium oxide manganese transparent dispersion.
[0070] Dissolve 0.01 mol of Ni(NO3)·6H2O in 100 mL of anhydrous ethanol. Then add a certain amount of the above-prepared nano-zirconium oxide manganese mixed oxide suspension to the nickel nitrate solution at a molar ratio of Ni:Mn:Zr=40:3:3. -1 Na2CO3 solution (0.5mol / L, 50ml) was injected into the precursor salt solution through a syringe pump (1ml / min), and the pH value of the solution was controlled at about 9. The obtained precipitate was further aged at room temperature for 1 hour and then filtered, and then washed with deionized water at room temperature. The obtained material was dried in air at 75°C overnight and then calcined in static air at 400°C for 3 hours. After the calcination, it was reduced at 450°C in a hydrogen atmosphere for 3 hours. The solid powder obtained by reduction was the prepared reverse phase catalyst, recorded as ZrMnO4 / Ni.
[0071] The solid catalyst is granulated into 60-80 mesh and placed in a gas-solid phase reactor for carbon dioxide methanation reaction. A reaction gas with a molar ratio of carbon dioxide to hydrogen of 1:4 is introduced, and the space velocity is 21000 to 127000 h -1 , the reaction pressure is normal pressure, and the reaction temperature is 130-320°C.
[0072] Example 2
[0073] Dissolve zirconium chloride and titanium tetrachloride in 50mL water at a concentration of 0.075mol / L, stir until completely dissolved, add zirconium chloride and titanium tetrachloride solutions to 50mL 2.5% ammonia solution and stir for 2h to obtain zirconium hydroxide and titanium hydroxide sol, and finally add to 20mL anhydrous ethanol to obtain ethanol zirconium and ethanol titanium sol. Add 5g of ethanol zirconium and ethanol titanium sol to a mixed solution of oleic acid: oleylamine: ethanol (40mL: 5mL: 5mL) and stir evenly, then transfer to a 100ml polytetrafluoroethylene-lined autoclave. Subsequently, seal the autoclave and heat at 200℃ for 12h, wash the resulting precipitate with deionized water several times until the pH of the washing solution is neutral, freeze-dry overnight to obtain nano zirconium oxide titanium, and then disperse it in ethanol to obtain a nano zirconium titanium oxide solid solution transparent dispersion.
[0074] Dissolve 0.01 mol of Ni(NO3)6H2O in 100 mL of anhydrous ethanol. Then add a certain amount of the above prepared nano-zirconium oxide titanium mixed oxide suspension to the nickel nitrate solution at a molar ratio of Ni:Ti:Zr=40:3:3. -1 Na2CO3 solution (0.5mol / L 50ml) was injected into the precursor salt solution through a syringe pump (1ml / min), and the pH value of the solution was controlled at about 9. The obtained precipitate was further aged at room temperature for 1 hour and then filtered, and then washed with deionized water at room temperature. The obtained material was dried in air at 75°C overnight and then calcined in static air at 400°C for 3 hours. After the calcination, it was reduced at 450°C in a hydrogen atmosphere for 3 hours. The solid powder obtained by reduction was the prepared reverse phase catalyst, recorded as ZrTiO4 / Ni.
[0075] The solid catalyst was granulated into 60-80 mesh and placed in the gas-solid phase for carbon dioxide methanation reaction. The reaction gas with a molar ratio of carbon dioxide to hydrogen of 1:4 was introduced, and the space velocity was 21000h -1 , the reaction pressure is normal pressure, and the reaction temperature is 130-320°C.
[0076] Example 3
[0077] Except that the precursor salts are nickel nitrate hexahydrate, titanium tetrachloride and cerium chloride, the rest is the same as Example 2.
[0078] Example 4
[0079] Except that the precursor salts are nickel nitrate hexahydrate, aluminum chloride and zirconium chloride, the rest is the same as Example 1.
[0080] Example 5
[0081] The above method is the same as Example 1 except that the carrier precursor salt is nickel nitrate hexahydrate and aluminum nitrate nonahydrate, and the supported oxide precursor salt is zirconium chloride and manganese chloride, wherein the molar ratio of Ni / Al / Zr / Mn is 30 / 10 / 3 / 3.
[0082] Example 6
[0083] Except that the carrier precursor salt is cobalt nitrate hexahydrate, the rest is the same as Example 1.
[0084] Example 7
[0085] The above method is the same as Example 1 except that the carrier precursor salt is nickel nitrate hexahydrate and cobalt nitrate hexahydrate, and the supported oxide precursor salt is zirconium chloride and manganese chloride, wherein the molar ratio of Ni / Co / Zr / Mn is 30 / 10 / 3 / 3.
[0086] Example 8
[0087] Dissolve zirconium chloride and manganese chloride in 50 mL of water at a concentration of 0.075 mol / L, stir until completely dissolved, add zirconium chloride and manganese chloride solutions to 50 mL of 2.5% ammonia solution and stir for 2 hours to obtain zirconium hydroxide and manganese hydroxide sols, and finally add to 20 mL of anhydrous ethanol to obtain ethanol zirconium and ethanol manganese sols. Add 5 g of ethanol zirconium and ethanol manganese sols to a mixed solution of oleic acid: oleylamine: ethanol (40 mL: 5 mL: 5 mL) and stir evenly, then transfer to a 100 ml polytetrafluoroethylene lined autoclave. Subsequently, seal the autoclave and heat at 200 ° C for 12 hours, wash the resulting precipitate with deionized water several times until the pH of the washing solution is neutral, freeze-dry overnight to obtain nano zirconium oxide manganese, and then disperse it in ethanol to obtain a nano zirconium oxide manganese mixed oxide transparent dispersion.
[0088] Dissolve 0.01 mol of Ni(NO3)·6H2O in 100 mL of anhydrous ethanol. Then add a certain amount of the prepared nano-zirconium oxide manganese mixed oxide suspension to the nickel nitrate solution at a molar ratio of Ni:Mn:Zr=40:3:3. -1 Na2CO3 solution (0.5 mol / L 50 ml) was injected into the precursor salt solution through a syringe pump (1 ml / min) to control the pH value of the solution at about 9. The obtained precipitate was further aged at room temperature for 1 hour and then filtered, and then washed with deionized water at room temperature. The obtained precipitate was dried in air at 75°C overnight.
[0089] 0.32 ml of ruthenium trichloride solution (13.89 mg / ml) was diluted to 15 ml with deionized water, then stirred vigorously and 1.0 g of the above dried precipitate was added. The suspension was then evaporated to dryness in a 60°C water bath and then dried at 110°C. The obtained solid was represented as ZrMnO x / Ni-Ru, calcined in air at 400°C for 3h. After calcination, reduced at 450°C for 3h in a hydrogen atmosphere. The solid powder obtained by reduction is the prepared reverse phase catalyst, recorded as ZrMnO4 / Ni-Ru.
[0090] Example 9
[0091] The method is the same as Example 1 except that the carrier precursor salt is nickel nitrate hexahydrate, the supported metal oxide precursor salt is zirconium chloride, and the Ni / Zr molar ratio is 40 / 6.
[0092] Example 10
[0093] The method is the same as Example 1 except that the carrier precursor salt is nickel nitrate hexahydrate, the loaded metal oxide precursor salt is manganese nitrate hexahydrate, and the Ni / Mn molar ratio is 40 / 6.
[0094] Embodiment 11
[0095] The process is the same as Example 2 except that the carrier precursor salt is nickel nitrate hexahydrate, the supported oxide precursor salt is titanium tetrachloride, and the Ni / Ti molar ratio is 40 / 6.
[0096] Example 12
[0097] The method is the same as Example 1 except that the carrier precursor salt is nickel nitrate hexahydrate, the loaded metal oxide precursor salt is aluminum chloride, and the Ni / Al molar ratio is 40 / 6.
[0098] Example 13
[0099] Dissolve zirconium chloride and manganese chloride in 50 mL of water at a concentration of 0.075 mol / L, stir until completely dissolved, add zirconium chloride and manganese chloride solutions into 50 mL of 2.5% ammonia solution and stir for 2 hours to obtain zirconium hydroxide and manganese hydroxide sols, and finally add into 20 mL of anhydrous ethanol to obtain ethanol zirconium and manganese sols. Add 5 g of ethanol zirconium and manganese sols into a mixed solution of oleic acid: oleylamine: ethanol (40 mL: 5 mL: 5 mL) and stir evenly.
[0100] The sheet-like nickel foam (0.47 g) with a length of 3 cm, a width of 2 cm and a thickness of 2 mm was ultrasonically treated with diluted hydrochloric acid (2 mol / L), ethanol and deionized water for 30 min respectively. The treated nickel foam was immersed in the above-mentioned ethanol zirconium (0.0006 mol) and ethanol manganese (0.0006 mol) sol (Zr:Mn=1:1) in a 100 mL polytetrafluoroethylene-lined autoclave. Subsequently, the autoclave was sealed and heated at 200°C for 12 hours. The obtained nickel foam was washed with deionized water several times, and the obtained material was dried in air at 75°C overnight, and then calcined in static air at 400°C for 3 hours. After the calcination, it was reduced at 450°C in a hydrogen atmosphere for 3 hours. The reduced sheet material was the prepared reverse phase catalyst, recorded as ZrMnO4 / NF.
[0101] The solid catalyst has a particle size of 60-80 mesh and is placed in a gas-solid phase reactor for carbon dioxide methanation reaction. A reaction gas with a molar ratio of carbon dioxide to hydrogen of 1:4 is introduced, and the space velocity is 21000 to 127000 h -1 , the reaction pressure is normal pressure, and the reaction temperature is 180-320°C.
[0102] Comparative Example 1
[0103] Except that the molar ratio of Ni / Zr / Mn is 40 / 1 / 9, the rest is the same as Example 1.
[0104] Comparative Example 2
[0105] Except that the molar ratio of Ni / Zr / Mn is 40 / 9 / 1, the rest is the same as Example 1.
[0106] Comparative Example 3
[0107] Except that the molar ratio of Ni / Zr / Mn is 6 / 20 / 20, the rest is the same as Example 1.
[0108] Comparative Example 4
[0109] Except that the Ni / Mn molar ratio is 6 / 40, the rest is the same as Example 1.
[0110] Comparative Example 5
[0111] Except that the Ni / Zr molar ratio is 6 / 40, the rest is the same as Example 1.
[0112] Comparative Example 6
[0113] Except that the precipitant is ammonium carbonate, the rest is the same as Example 1.
[0114] Comparative Example 7
[0115] Except that the precipitant is ammonium oxalate, the rest is the same as Example 1.
[0116] Comparative Example 8
[0117] Except that the precipitant is ammonia water, the rest is the same as Example 1.
[0118] Comparative Example 9
[0119] Except that the precipitant is sodium hydroxide, the rest is the same as Example 1.
[0120] Comparative Example 10
[0121] Dissolve zirconium chloride and manganese chloride in 50mL water at a concentration of 0.075mol / L, stir until completely dissolved, add zirconium chloride and manganese chloride solutions to 50mL 2.5% ammonia solution and stir for 2h to obtain zirconium hydroxide and manganese hydroxide sols, and finally add to 20mL anhydrous ethanol to obtain ethanol zirconium and ethanol manganese sols. Add 5g of ethanol zirconium and ethanol manganese sols to a mixed solution of oleic acid: oleylamine: ethanol (40mL: 5mL: 5mL) and stir evenly, then transfer to a 100ml polytetrafluoroethylene-lined autoclave. Subsequently, seal the autoclave and heat at 200℃ for 12h, wash the resulting precipitate with deionized water several times until the pH of the washing solution is neutral, freeze-dry overnight to obtain nano zirconium dioxide manganese mixed oxide, and then disperse it in ethanol to obtain a nano zirconium dioxide manganese mixed oxide transparent dispersion.
[0122] 1 g of P123 was dissolved in 50 ml of deionized water and transferred to a 50 ml polytetrafluoroethylene-lined autoclave. Then 0.9 g of nickel nitrate hexahydrate, 0.9 g of urea and 25 mL of deionized water were added to the above suspension to form a stock solution. Subsequently, the autoclave was sealed and heated at 140 ° C for 12 h, and the precipitate was collected by centrifugation, washed with deionized water and ethanol, and freeze-dried overnight. The obtained solid was heated in a tube furnace at 400 ° C for 3 h to obtain NiO powder.
[0123] Disperse 0.01 mol of nickel oxide powder in 100 mL of anhydrous ethanol and add it to a round-bottom flask. Then add a certain amount of the above-prepared nano-zirconium oxide manganese mixed oxide suspension to the round-bottom flask at a molar ratio of Ni:Mn:Zr=40:3:3. Then stir for 0.5 h and then ultrasonicate for 1 h to achieve good dispersion of the slurry. Then, condense and reflux the slurry at 70 ° C for 2 h. Transfer the flask to a rotary evaporator, heat to 60 ° C, control the speed to 200 r / min, spin dry the solution, and freeze-dry the resulting precipitate overnight.
[0124] After freeze drying, the catalyst was reduced at 400℃ for 2h in a hydrogen atmosphere. The solid powder (ZrMnO4 / Ni) obtained by reduction was the prepared catalyst. The particle size of the solid catalyst was 60-80 mesh and placed in the gas-solid phase for carbon dioxide methanation reaction. The reaction gas with a molar ratio of carbon dioxide to hydrogen of 1:4 was introduced, and the space velocity was 21000h -1 , the reaction pressure is normal pressure, and the reaction temperature is 150-300°C.
[0125] Comparative Example 11
[0126] The above method is the same as Comparative Example 10 except that the carrier precursor salt is nickel nitrate hexahydrate, the precursor salt of the supported metal oxide is manganese chloride, and the Ni / Mn molar ratio is 40 / 6.
[0127] Comparative Example 12
[0128] The above method is the same as Comparative Example 10 except that the carrier precursor salt is nickel nitrate hexahydrate, the precursor salt of the supported metal oxide is zirconium chloride, and the Ni / Zr molar ratio is 40 / 6.
[0129] Comparative Example 13
[0130] The preparation method is the same as that of Example 1 except that the carrier precursor salt is cobalt nitrate hexahydrate, the precursor salts of the supported metal oxide are zirconium chloride and manganese chloride, and the molar ratio of Co / Zr / Mn is 6 / 20 / 20.
[0131] Comparative Example 14
[0132] The process is the same as that of Example 2 except that the carrier precursor salt is nickel nitrate hexahydrate, the precursor salt of the supported metal oxide is tetrabutyl titanate, and the Ni / Ti molar ratio is 6 / 40.
[0133] Comparative Example 15
[0134] The process is the same as in Example 1 except that the carrier precursor salt is nickel nitrate hexahydrate, the precursor salt of the supported metal oxide is aluminum chloride, and the Ni / Al molar ratio is 6 / 40.
[0135] Comparative Example 16
[0136] The method is the same as Example 1 except that the carrier precursor salt is nickel nitrate hexahydrate, the precursor salt of the supported metal oxide is magnesium chloride, and the Ni / Mg molar ratio is 6 / 40.
[0137] Comparative Example 17
[0138] Glucose (0.01 mol) and acrylamide (0.015 mol) were stirred and dissolved in deionized water (80 mL), and then cerium nitrate hexahydrate (0.0045 mol) and lanthanum nitrate hexahydrate (0.0005 mol) were added to form a transparent solution. Then 3.2 mL of 25 wt% ammonia solution was added dropwise with stirring, and the pH value was controlled to be maintained at about 10. After stirring for 5 hours, it was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was hydroheated at 180 ° C for 72 hours, and after cooling to room temperature, the solid precipitate was collected by filtration and washed with deionized water and anhydrous ethanol several times. Dry at 100 ° C for 10 hours, calcine at 600 ° C for 2 hours, and the heating rate was 5 ° C min -1 , recorded as La-CeO2-600.
[0139] Nickel nitrate hexahydrate (0.165 g) was dissolved in a certain amount of ethylene glycol (0.2 mL), and then the solution was added dropwise to the prepared carrier (0.3 g), sealed at 40 °C for 24 h, dried at 100 °C for 12 h, and then heated in air at 5 °C min -1 The catalyst was calcined at 400℃ for 2h at a heating rate of 1.5℃. After calcination, the catalyst was reduced at 400℃ for 2h in a hydrogen atmosphere. The reduced Ni / La-CeO2 was the prepared catalyst. [1] .
[0140] Comparative Example 18
[0141] A certain amount of nickel nitrate hexahydrate and ruthenium nitrate solution were mixed in 40 mL of deionized water, and then a certain amount of Ce 0.5 Zr 0.5 O2 (commercial), then the suspension was evaporated to dryness in a 50°C water bath and then dried at 110°C. The obtained solid was represented as Ni-Ru / CeZrO x , calcined in air at 400℃ for 3h, and then reduced in hydrogen atmosphere at 400℃ for 2h to obtain Ni-Ru / Ce 0.5 Zr 0.5 O2 is the prepared catalyst [2] .
[0142] Comparative Example 19
[0143] A certain amount of nickel nitrate hexahydrate and ruthenium nitrate solution were mixed in 40 mL of deionized water, and then a certain amount of Ce 0.5 Al 0.5 O2 (commercial), then the suspension was evaporated to dryness in a 50°C water bath and then dried at 110°C. The obtained solid was calcined in air at 400°C for 3h. After the calcination, it was reduced in a hydrogen atmosphere at 400°C for 2h to reduce the obtained Ni-Ru / Ce 0.5 Al0.5 O2 is the prepared catalyst [2] .
[0144] Comparative Example 20
[0145] Nickel nitrate hexahydrate (0.297 g) and manganese acetate tetrahydrate (0.501 g) were dissolved in 6 mL of deionized water. An appropriate amount of TiO2 (about 2 g) was slowly added to the aqueous solution under stirring at room temperature. The suspension was left for 3 hours and then heated to 80°C to remove excess H2O. Finally, the obtained solid was dried overnight at 110°C in a static air oven. The obtained Ni-Mn / TiO2 was the prepared catalyst. [3] .
[0146] Comparative Example 21
[0147] Nickel nitrate hexahydrate (0.44 g, 1.50 mmol), aluminum nitrate nonahydrate (0.19 g, 0.50 mmoL), zirconium nitrate pentahydrate (0.02 g, 0.005 mmoL) and urea (0.60 g, 10.00 mmoL) were dissolved in deionized water (70 mL). Subsequently, the mixed solution was placed in a Teflon-lined autoclave and subjected to a hydrothermal reaction at 120 °C for 12 h. The solid product was obtained by centrifugation, washed with deionized water and ethanol until the solution pH was close to 7, and dried at 80 °C for 15 h. It was named Ni 0.73 Zr 0.03 Al 0.24 -LDH. 0.73 Zr 0.03 Al 0.24 -LDH was reduced in H2 gas at 600℃ for 2h (heating rate was 5℃ / min -1 , H2 flow rate was 50 mL min -1 The catalyst prepared is obtained after [4] .
[0148] Comparative Example 22
[0149] The treated cylindrical nickel foam with a length of 5 cm and a diameter of 2 cm was immersed in a solution containing nickel nitrate hexahydrate (0.009 mol), aluminum nitrate nonahydrate (0.0015 mol), iron nitrate (0.0015 mol) and urea (0.04 mol) and stirred for 30 min, and then transferred to a 100 mL polytetrafluoroethylene-lined autoclave. Subsequently, the autoclave was sealed and heated at 110 ° C for 8 h. The resulting precursor was washed several times with deionized water and dried in air at 65 ° C for 12 h. Finally, the Ni-Fe-Al / NF obtained by in-situ reduction of the precursor in a tubular furnace at 500 ° C at a heating rate of 2 ° C / min in a flowing H2 / N2 atmosphere (1 / 10, V / V) is the prepared catalyst. [5] .
[0150] Comparative Example 23
[0151] Dissolve cerium nitrate hexahydrate and chromium nitrate nonahydrate in 30 mL of deionized water with a Cr / Ce molar ratio of 1:9. Add ammonia solution dropwise to the precursor salt solution while stirring continuously until complete precipitation at pH = 10. Filter the mixture to collect the precipitate and wash it repeatedly with deionized water. Dry the solid at 110 ° C overnight and calcine at 500 ° C for 4 h to obtain the Cr-CeO2 support.
[0152] Cr-CeO2 was impregnated into an aqueous solution of RuCl3·3H2O. The mixture was vigorously stirred and evaporated in a water bath at 70°C for 4 hours, and then further dried at 110°C overnight. The resulting solid was named RuO2 / Cr-CeO2, calcined in air at 500°C for 4 hours, and then reduced in a hydrogen atmosphere at 400°C for 2 hours. The resulting Ru / Cr-CeO2 was the prepared catalyst. [6] .
[0153] Comparative Example 24
[0154] Ru-TiO2: Dilute 0.6 g of ruthenium trichloride hydrate to 50 mL with deionized water, then stir vigorously and add 2.0 g of anatase titanium dioxide. Then, evaporate the suspension to dryness in a 50 ° C water bath and then dry it at 110 ° C. The obtained solid is denoted as Ru / TiO2 and calcined in air at 400 ° C for 3 h. Then, the sample is repeatedly washed with a dilute ammonia solution to remove residual chloride, and the sample is dried at 60 ° C overnight. The resulting Ru / TiO2 is the prepared catalyst. The loading of Ru in the Ru / TiO2 catalyst is 10wt%.
[0155] Comparative Example 25
[0156] Commercial Ru / Al2O3
[0157] Except for using Ru-TiO2 and commercial Ru-Al2O3 and the reduction temperature being 200°C, everything else is the same as Example 1.
[0158] Table 1 shows the CO2 conversion rate of each catalyst in the CO2 methanation reaction.
[0159] Table 1 CO2 conversion rate of each catalyst for CO2 methanation reaction
[0160]
[0161]
[0162] a: The substance was not detected and the content is negligible.
[0163] Compared with the comparative example, Examples 1 to 13 in Table 1 showed higher low-temperature CO2 methanation activity, reflecting the superiority of the reverse oxide / metal catalyst over the traditional forward metal / oxide low-temperature catalytic CO2 methanation.
[0164] Figure 1 The thermodynamic diagram of CO2 methanation reaction and the side reaction reverse water gas shift reaction with temperature is given. Methanation reaction is a strong exothermic reaction, and low temperature is conducive to the reaction. Reverse water gas shift reaction is an endothermic reaction, and high temperature is conducive to the formation of CO.
[0165] Figure 2 The reaction results of Examples 1, 9, 10 and Comparative Examples 1, 2, 3, 24, 25 in the range of 130-320°C are compared. x / Ni catalyst showed excellent performance at 170-180℃ and at 21000h -1 The CO2 conversion performance close to the equilibrium conversion rate can be achieved at the space velocity, and the target product methane selectivity is >99.9%, far exceeding the performance of commercial Ru / Al2O3 catalysts and Ru / TiO2 catalysts. x The forward catalyst of the oxide solid solution must be above 260°C to achieve a CO2 conversion rate of more than 50%.
[0166] Figure 3 Example 1 is given at 190°C, 21000-127000h -1 The results of methanogenic activity in the range of air velocity show that the reverse ZrMnO x The / Ni catalyst still maintains high CO2 conversion and nearly 100% methane selectivity.
[0167] Figure 4The stability test results of Example 1 at 180°C for 1500 hours are given. After running for 1500 hours, there is no obvious change in the catalyst activity.
[0168] Figure 5 The reaction results of Example 1 and Comparative Examples 6, 7, 8, and 9 are given. By comparing different precipitated sodium carbonate, ammonia water, ammonium carbonate, ammonium oxalate, and sodium hydroxide, high-performance low-temperature methanation reverse catalysts can be prepared, among which sodium carbonate has the best effect as a precipitant.
[0169] Figure 6 The reaction results of Examples 1, 6, 7 and Comparative Example 13 in the range of 130-220°C are given. Compared with the inverse ZrMnO x / Ni catalyst, cobalt doping leads to a certain degree of reduction in activity, Co is loaded on ZrMnO x The forward catalytic activity of the oxide solid solution is significantly lower than that of the reverse phase.
[0170] Table 1 compares the results of Examples 1, 9, 10, 13 with Comparative Examples 10, 11, 12. Reverse methanation catalysts with excellent performance can be synthesized by volume impregnation method, deposition precipitation method and porous monolithic catalyst impregnation oxide nanoparticle precursor salt preparation method.
[0171] Figure 7 The reaction results of Examples 9-10 and Comparative Examples 4-5 are given, and it can be seen that the trend is consistent with that of the ternary reverse catalyst, and the binary reverse catalyst also has a reaction performance that is superior to that of the traditional forward catalysis.
[0172] Figure 8 This is the HAADF-STEM photo of the catalyst prepared in Example 1. It can be seen that the particle size of the metal carrier of the catalyst prepared in the present invention is about 10 nm, and the oxide is evenly dispersed on the metal carrier.
[0173] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0174] References
[0175] [1]Zhang T,Wang W,Gu F,et al.Enhancing the low-temperature CO2methanation over Ni / La-CeO2 catalyst:The effects of surface oxygen vacancyand basic site on the catalytic performance[J].Applied Catalysis B:Environmental,2022,312:121385.
[0176] [2]Merkouri L P,Le SachéE,Pastor-Pérez L,et al.Versatile Ni-Rucatalysts for gas phase CO2 conversion:Bringing closer dry reforming,reversewater gas shift and methanation to enable end-products flexibility[J].Fuel,2022,315:123097.
[0177] [3]Vrijburg W L,Moioli E,Chen W,et al.Efficient base-metal NiMn / TiO2catalyst for CO2 methanation[J].Acs Catalysis,2019,9(9):7823-7839.
[0178] [4]He F,Zhuang J,Lu B,et al.Ni-based catalysts derived from Ni-Zr-Alternary hydrotalcites show outstanding catalytic properties for low-temperature CO2 methanation[J].Applied Catalysis B:Environmental,2021,293:120218.
[0179] [5]Gao Y,Dou L,Zhang S,et al.Coupling bimetallic Ni-Fe catalysts andnanosecond pulsed plasma for synergistic low-temperature CO2 methanation[J].Chemical Engineering Journal,2021,420:127693.
[0180] [6]Xu X,Liu L,Tong Y,et al.Facile Cr 3+ -doping strategy dramaticallypromoting Ru / CeO2 for low-temperature CO2 methanation:Unraveling the roles ofsurface oxygen vacancies and hydroxyl groups[J].ACS Catalysis,2021,11(9):5762-5775.
Claims
1. A solid reverse phase catalyst, characterized in that: The solid reverse phase catalyst uses a metal that dissociates hydrogen as a carrier and a nano-oxide that generates oxygen vacancies to adsorb and activate carbon dioxide as a support phase. The nano-oxide is evenly dispersed on the surface of the metal carrier and has a nano-oxide / metal reverse phase interface structure. in, The support metal is selected from nickel, nickel-aluminum or nickel-cobalt; The supported phase nano-oxide is selected from manganese oxide and zirconium oxide; Based on the total molar amount of the metal in the carrier and the supported phase, the molar fraction of the metal in the supported phase is 0.01 to 30%; The preparation method of the solid reverse phase catalyst comprises the following steps: (1) Synthesis of Nano-Oxides The precursor salt of the load phase is dissolved in a solvent, and the obtained solution is added to a precipitant solution to obtain a hydroxide sol; the obtained hydroxide sol is added to ethanol to obtain a hydroxide-ethanol sol; the hydroxide-ethanol sol is then dispersed in a mixed solution of oleic acid / oleylamine / ethanol, stirred evenly, transferred to an autoclave, sealed, and subjected to solvent thermal treatment at 80 to 220° C. for 1 to 24 hours, after which a solid product is collected, washed with deionized water until the pH of the washing solution is neutral, and freeze-dried to obtain a nano-oxide, which is dispersed in ethanol to obtain a nano-oxide dispersion for standby use; Wherein, the precursor salt of the supported phase is a manganese salt and a zirconium salt; the manganese salt is selected from manganese nitrate, hydrated manganese nitrate, and manganese chloride; the zirconium salt is selected from zirconium nitrate, hydrated zirconium nitrate, and zirconium chloride; (2) Synthesis of solid reverse phase catalyst The precursor salt of the carrier is dissolved in a solvent, and the nano-oxide dispersion prepared in step (1) is added dropwise to the obtained solution, and then a precipitant solution is added dropwise under stirring, and the pH is controlled to be 9, followed by aging at room temperature, filtering, washing, drying, calcining in static air, and reducing in a hydrogen atmosphere after the calcination to obtain a solid reverse phase catalyst; Among them, the precursor salt of the carrier is a nickel salt, a nickel salt-aluminum salt or a nickel salt-cobalt salt; the nickel salt is selected from nickel nitrate, hydrated nickel nitrate, and nickel chloride; the aluminum salt is selected from hydrated aluminum nitrate; and the cobalt salt is selected from cobalt nitrate, hydrated cobalt nitrate, and cobalt chloride.
2. The solid reverse phase catalyst according to claim 1, characterized in that In step (1) or step (2) of the preparation method, the solvent is selected from one or more of water, methanol, ethanol, butanol, tetrahydrofuran, and methyl tert-butyl ether.
3. The solid reverse phase catalyst according to claim 1, characterized in that In step (1) or step (2) of the preparation method, the precipitant is selected from one or more of ammonium carbonate, ammonia water, urea, sodium hydroxide, sodium bicarbonate, ammonium oxalate, and oxalic acid.
4. The solid reverse phase catalyst according to claim 1, characterized in that In step (2) of the preparation method, the calcination temperature is 200 to 600° C. and the calcination time is 1 to 12 hours.
5. The solid reverse phase catalyst according to claim 1, characterized in that In step (2) of the preparation method, the reduction temperature is 200-700° C., and the time is 1-6 hours; the hydrogen concentration in the reducing atmosphere is in the range of 5-100%, and the total flow rate is in the range of 5-100 ml / min.
6. Use of the solid reverse phase catalyst as claimed in claim 1 in carbon dioxide methanation reaction.
7. The use according to claim 6, characterized in that The method of application is: The solid reverse phase catalyst is placed in a fixed bed reactor, and a reaction gas with a molar ratio of carbon dioxide to hydrogen of 1:4 is introduced at a volume space velocity of 9000-127000 h -1 The reaction pressure range is from normal pressure to 6Mpa, and the reaction temperature range is from 25 to 450°C.